FORMATION OF COMMUNICATIVE CULTURE OF STUDENTS BY MEANS OF BUSINESS GAMES IN CLASSES FROM A FOREIGN LANGUAGE - K.H. Vyshnevska (Academy of Cognitive and Natural Sciences, 2022)
The article investigates the problems communication culture able to business-playing the development of students' Creative abilities while learning a foreign language.